PENGEMBANGAN BUKU PENGAYAAN DIALOG DI LINGKUNGAN KELUARGA BERBASIS UNGGAH-UNGGUH UNTUK SISWA SMP DI KABUPATEN SEMARANG - Nurcahyaningrum, Desiyana Rendryasari (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2018)
This research was based on the lack of the enrichment books containing Javanese language dialogues in accordance with the unggah-ungguh in Semarang regency. Therefore, this study developed the enrichment books of dialogue in family environment based on unggah-ungguh to support the studying and writing dialogue text. This study used research and development design. The research data was the data of teacherâ€™s and studentâ€™s needs, expert validation, and product trials. The result of this study was the enrichment book containing collection of dialogues in the family environment based on unggah-ungguh with the title â€œTepa Palupiâ€. The book had improved after being validated by expert lecturers and users. Experimental result showed that the enrichment book of dialogue in family environment based on unggah-ungguh can improve student achievement. The test results on the examining dialogue text competence increased 7,4%, where as the writing dialogue text competence increased 17.2%. The improvement was followed by an attitude of students to be more active, enthusiastic, and very interested in reading the enrichment books used in the learning. Keywords: the enrichment books, dialogue, family environment, unggah-ungguh